5x-3(x-2)=-7+4x-3

Simple and best practice solution for 5x-3(x-2)=-7+4x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3(x-2)=-7+4x-3 equation:


Simplifying
5x + -3(x + -2) = -7 + 4x + -3

Reorder the terms:
5x + -3(-2 + x) = -7 + 4x + -3
5x + (-2 * -3 + x * -3) = -7 + 4x + -3
5x + (6 + -3x) = -7 + 4x + -3

Reorder the terms:
6 + 5x + -3x = -7 + 4x + -3

Combine like terms: 5x + -3x = 2x
6 + 2x = -7 + 4x + -3

Reorder the terms:
6 + 2x = -7 + -3 + 4x

Combine like terms: -7 + -3 = -10
6 + 2x = -10 + 4x

Solving
6 + 2x = -10 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
6 + 2x + -4x = -10 + 4x + -4x

Combine like terms: 2x + -4x = -2x
6 + -2x = -10 + 4x + -4x

Combine like terms: 4x + -4x = 0
6 + -2x = -10 + 0
6 + -2x = -10

Add '-6' to each side of the equation.
6 + -6 + -2x = -10 + -6

Combine like terms: 6 + -6 = 0
0 + -2x = -10 + -6
-2x = -10 + -6

Combine like terms: -10 + -6 = -16
-2x = -16

Divide each side by '-2'.
x = 8

Simplifying
x = 8

See similar equations:

| 13=-6+k | | 6x-4=-x | | -53+12x=3x+100 | | 16t^2-90t+90=0 | | 4-3y=3-4y | | 5b+8-6b= | | 3x-5/3=96 | | 100=(4*w)*w | | 41790=5(210t) | | 100=(4xw)xw | | -n-21=8-3(n+7) | | 8x-10=7x+2 | | 13-4=x | | x^2-3=a | | ((-5)*c)+(8*c)= | | 2a-8=4(3a+1)-7 | | 2x-19=3x | | -7a+8b=25 | | x^2+.4+3=0 | | 4sin^2x-4sinx-9=0 | | 4x+5=48 | | 7+x=-4x+117 | | 3s-5= | | -5x-17/-4=-7 | | 3(s-5)= | | (x-2)(x-i)=0 | | 12x-48=36 | | 3cosx-2x=0 | | (2b-68)+(b-3)=180 | | 5t+20a=0 | | 26-9y=-4 | | 2w+8=10 |

Equations solver categories